Burnout Coping Management among Oil and Gas Workers: A Systematic Literature Review - Patria Rahmawaty; Luh Putu Mahyuni; Agus Fredy Maradona (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Employees in the oil and gas industry face unique occupational stressors that increase their vulnerability to burnout, including long working hours, hazardous conditions, and operational uncertainty. This study synthesizes empirical evidence on coping mechanisms used by oil and gas workers to manage burnout at individual, social, and organizational levels. Using a systematic literature review based on the PRISMA 2020 protocol, this review examined Scopus-indexed peer-reviewed articles published between 2007 and 2025 through Boolean search strategies and keywords related to burnout, coping, and the oil and gas workforce. Following a staged screening process, seven articles met the inclusion criteria and were analyzed using thematic analysis. The findings reveal five main domains of coping strategies among oil and gas workers: problem-focused coping, emotion-focused coping, social support-based coping, resilience-oriented coping, and organizational coping. These findings indicate that burnout management depends not only on individual capacity but also on social support, work design, and organizational policies. This article develops an integrated model of burnout coping management for oil and gas workers that links individual psychological resilience with organizational interventions to enhance well-being, occupational safety, and workforce sustainability in high-risk work environments.